2009
DOI: 10.1073/pnas.0910216107
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating cation/fatty acid anion pair as a mitochondria-targeted protonophore

Abstract: A unique phenomenon of mitochondria-targeted protonophores is described.ItconsistsinatransmembraneH þ -conductingfattyacidcycling mediated by penetrating cations such as 10-(6'-plastoquinonyl) decyltriphenylphosphonium (SkQ1) or dodecyltriphenylphosphonium (C 12 TPP). The phenomenon has been modeled by molecular dynamics and directly proved by experiments on bilayer planar phospholipid membrane, liposomes, isolated mitochondria, and yeast cells. In bilayer planar phospholipid membrane, the concerted action of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(122 citation statements)
references
References 29 publications
(36 reference statements)
4
115
1
Order By: Relevance
“…However, the existence of ⌬ on the inner mitochondrial membrane being negative inside makes cationic compounds capable of being accumulated inside mitochondria, which should increase their efficiency. It has been shown that SkQR1 accumulates effectively in mitochondria (experiments on isolated mitochondria, mammalian cell cultures, yeast cells, and intact organisms (7,53,54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the existence of ⌬ on the inner mitochondrial membrane being negative inside makes cationic compounds capable of being accumulated inside mitochondria, which should increase their efficiency. It has been shown that SkQR1 accumulates effectively in mitochondria (experiments on isolated mitochondria, mammalian cell cultures, yeast cells, and intact organisms (7,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…The force field parameters for C 12 -TPP were taken from Ref. 7, and parameters for SkQR1 were developed using those for sulforhodamine (36). All molecular dynamics calculations were performed at the supercomputer SKIF "Chebyshev" in the Computation Center, Moscow State University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive charge is not localized but spread over the aromatic rings, thus allowing for membrane permeation due to the already negative potential of cells with respect to their outside and even more so of mitochondria, the only human organelle with a negative potential with respect to the cytoplasm. Once inside, they are trapped by the opposite potential outside (Severin et al, 2010 The fluorescence half-life of 1 in mitochondria was studied under a variety of conditions. Data are summarized in Table I together with those from the coumaryl derivative 2.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the current obesity epidemic, and illicit sales via the internet, it is alarming to see that DNP has made a comeback as a weight loss agent, with predictable lethal results [235,236]. Thus, while mitochondrial uncoupling with DNP does not appears to be a safe weight-loss therapy, other more recently described uncoupling agents may potentially have a safer profile for use in humans [237][238][239]. An additional approach may to be to upregulate physiological uncoupling in brown adipose tissue, via sympathomimetic agents or agonists for thyroid hormone or bile acid receptors.…”
Section: Mitochondrial Uncouplingmentioning
confidence: 99%